What is a superior labial frenulum? An anatomical and histological study. Issue 1 (11th November 2022) - Iwanaga, Joe; He, Puhan; Fukino, Keiko; Hur, Mi‐Sun; Kim, Hee‐Jin; Han, Aya; Watanabe, Koichi; Ibaragi, Soichiro; Kitagawa, Norio; Tubbs, R. Shane
Abstract: Anatomy of the superior labial frenulum (SLF), at first glance, seems to be well established. However, existing studies on the SLF lack description of the incisivus labii superioris (ILS), which cannot be ignored when discussing the SLF. We believe that thorough understanding of the SLF necessitates the anatomical knowledge of the ILS. This study aimed to elucidate the anatomical relationship between the orbicularis oris (OO), ILS, and SLF. A total of 20 formalin fixed human cadaveric specimens were used for gross anatomical and/or histological observation. For histological observation, all specimens were stained with Masson‐trichrome. The SLF was a mucosal fold between the gingival mucosa and alveolar mucosa with connective tissue deep to it. The connective tissue attached to the alveolar bone in the junction between the right and left ILS. Skeletal muscle fibers other than orbicularis oris was found in one specimen, which were considered the ILS. During a frenulectomy, removal of the connective tissue bundle is required to prevent recurrence of the high SLF insertion.